1996
DOI: 10.21273/jashs.121.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Photon Flux, Photoperiod, and Temperature Effects on Emissions of (Z)-3-hexenal, (Z)-3-hexenol, and (Z)-3-hexenyl Acetate from Lettuce

Abstract: To investigate the effects of environment on plant volatile emissions, `Waldmann's Green' leaf lettuce was cultivated under different levels of photosynthetic photon flux (PPF), photoperiod, and temperature. A modified growth chamber was used to sample plant volatile emissions nondestructively, over time, and under controlled conditions. Total volatile emission rates were significantly higher from lettuce cultivated under PPF of 360 or 200 μmol·m-2·s-1 compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The release of some of the potential VOC signals are known to be influenced by abiotic factors such as nutrient availability (Schmelz et al 2003), temperature (Charron et al 1996), wind, UV radiation (Harley et al 1996;Zepp et al 1998;De Moraes et al 2004), and ozone exposure (Heiden et al 1999) in addition to wounding and herbivore attack. These contingencies, in addition to the ephemeral nature of the volatile signal, explain why most studies of plant-plant signaling have been performed in the laboratory (Arimura et al 2000a(Arimura et al , b, 2001Dicke and Bruin 2001;Engelberth et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The release of some of the potential VOC signals are known to be influenced by abiotic factors such as nutrient availability (Schmelz et al 2003), temperature (Charron et al 1996), wind, UV radiation (Harley et al 1996;Zepp et al 1998;De Moraes et al 2004), and ozone exposure (Heiden et al 1999) in addition to wounding and herbivore attack. These contingencies, in addition to the ephemeral nature of the volatile signal, explain why most studies of plant-plant signaling have been performed in the laboratory (Arimura et al 2000a(Arimura et al , b, 2001Dicke and Bruin 2001;Engelberth et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…First indications to support a role of GLV in photosynthesis came from a study by Charron et al [36]. They found that increased photosynthetic photon flux and the length of the photoperiod would cause an increase of GLV production and release in lettuce.…”
Section: Green Leaf Volatiles and Photosynthesismentioning
confidence: 99%
“…Plant volatiles are not emitted in the dark but their levels rise steadily as light intensity increases (Gouinguené and Turlings 2002). For example, enhanced light levels accelerate the release of C6-volatiles from Lactuca sativa L. plants (Charron et al 1996). Loreto et al (2006) have also found that high light causes increased emission of many VOCs, such as isoprene and acetaldehyde.…”
mentioning
confidence: 99%